Bismuth sodium titanate powder material and preparation method thereof

Through the two-step heating method, a bismuth titanate powder with a rhombus square phase was prepared, which solved the problems of poor dispersion, large particle size and second phase in the prior art, and achieved high purity, fine particles and good ferroelectric properties.

CN119751054AInactive Publication Date: 2025-04-04DANDONG GUOTONG ELECTRONICS COMPONENTS
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411966121.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the existing bismuth titanate nano powder preparation technology, poor dispersion, large particle size, second phase, and high mineralizer concentration, resulting in poor preparation efficiency and performance.

Method used

By using a two-step heating method, a bismuth nitrate pentahydrate, tetrabutyl titanate and sodium hydroxide were reacted under specific conditions to prepare a rhombic phase (Bi0.5Na0.5)TiO3 powder, whose particles are spherical aggregates composed of 50 nm cubes, with an average size of 450 nm.

Benefits of technology

The high purity, fine particles and good sintering performance of bismuth titanate nano powder were achieved, and the ferroelectric properties of the ceramics were improved. The maximum polarization strength, residual polarization strength and coercive field reached 40.02 μC/cm2, 27.78 μC/cm2 and 87.5 kV/cm respectively.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751054A_ABST
    Figure CN119751054A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of powder preparation through a wet chemical method, and provides a bismuth sodium titanate powder material and a preparation method thereof, the chemical formula of the material is (Bi0. 5Na0. 5) TiO3, particles of the material are spherical aggregates composed of 50 nm cubes, the average size of the particles is 450 nm, (Bi0. 5Na0. 5) TiO3 powder is subjected to hydrothermal synthesis through a two-step heating method, and the bismuth sodium titanate powder material has the advantages of being simple in process, low in cost, capable of being produced in a large scale and the like and has a good application prospect. The prepared (Bi0. 5Na0. 5) TiO3 powder has a wide application prospect in the fields of bismuth sodium titanate, bismuth sodium titanate-based ferroelectric ceramics, thermal sensitive ceramics and the like, the (Bi0. 5Na0. 5) TiO3 ceramic prepared by taking the prepared (Bi0. 5Na0. 5) TiO3 powder as a raw material and sintering at 1100 DEG C for 4 hours has good sinterability and ferroelectricity, the relative density of the ceramic is 95% or above, and the ceramic has a good application prospect in the fields of bismuth sodium titanate, bismuth sodium titanate-based ferroelectric ceramics, thermal sensitive ceramics and the like. The maximum polarization intensity, the remanent polarization intensity and the coercive field are 40.02 mu C / cm < 2 >, 27.78 mu C / cm < 2 > and 87.5 kV / cm respectively.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparing powders by wet chemical method, and in particular relates to a sodium bismuth titanate titanium powder material and a preparation method thereof. Background Art

[0002] Ferroelectric ceramics, as an important functional ceramic material, are widely used in the fields of machinery, electronics, aerospace, etc. At present, the ferroelectric ceramics used are mainly lead-based perovskite oxides, of which the content of PbO accounts for about 70% of the total material. PbO is a harmful substance. If it is not properly protected during the preparation, use and disposal of the material, it may cause harm to the environment and human body. Therefore, it is of great significance to develop lead-free ferroelectric ceramics with excellent performance and environmental friendliness. Sodium bismuth titanate ((Bi 0.5 Na 0.5 )TiO3, referred to as BNT) is a type of A-site composite substituted perovskite structure ferroelectric material with a relatively high Curie temperature (Tc = 320 ℃). Due to its good ferroelectricity, NBT is considered to be one of the most promising candidate materials for lead-free ferroelectric ceramics.

[0003] The crystal structure, particle size and morphology of NBT powder have a decisive influence on the preparation of high-performance NBT ceramics. Most of the preparation of NBT powder is prepared by the traditional solid-phase method, which has the advantages of mature technology, simple process and low cost. However, the raw materials used in the solid-phase synthesis method are often not fully dispersed, the chemical composition uniformity of the ceramic powder produced is insufficient, and it is difficult to obtain a single crystal phase, which affects the electrical properties of the sintered NBT ceramics. Compared with the traditional solid-phase method, the NBT powder synthesized by wet chemical methods such as sol-gel method and hydrothermal synthesis method has high purity, fine particles and good sintering performance, so it can improve the electrical properties of electronic NBT ceramics. Among these wet chemical methods, the hydrothermal method is considered to be one of the most effective methods for preparing high-purity and fine sodium bismuth titanate powder under mild conditions due to its low synthesis temperature, low cost, environmental friendliness and simple process. However, the sodium bismuth titanate nanopowder prepared according to the existing technology has poor dispersibility and large particle size. In addition to the rhombohedral phase NBT, it also contains a small amount of second phase, and the concentration of mineralizer required for preparation is relatively high and the time is long. Therefore, it is necessary to develop new bismuth titanate nanopowder preparation technology. Summary of the invention

[0004] The purpose of the present invention is to provide a bismuth titanate nanopowder material and a preparation method thereof, so as to solve the problems that the bismuth titanate nanopowder prepared by the prior art has poor dispersibility and large particle size.

[0005] The object of the present invention is achieved in that: A bismuth titanate nanopowder material, wherein the powder material is a rhombohedral phase (Bi 0.5 Na0.5 )TiO3, whose particles are spherical aggregates composed of 50 nm cubes with an average size of 450 nm.

[0006] In the above technical scheme, the main preparation raw materials include: bismuth nitrate pentahydrate Bi(NO3)3·5H2O, tetrabutyl titanate Ti(OC4H9)4, and sodium hydroxide NaOH as solutes, and deionized water, dilute nitric acid and anhydrous ethanol are used as solvents to prepare the precursor solution. At the same time, sodium hydroxide is also used as a mineralizer for the hydrothermal reaction.

[0007] A method for preparing sodium bismuth titanate powder material, the specific steps are as follows: Step 1: dissolving bismuth nitrate pentahydrate Bi(NO3)3·5H2O in ionized water, adding dilute nitric acid and stirring to obtain a clear and transparent solution a; Step 2: Dissolve tetrabutyl titanate Ti(OC4H9)4 in anhydrous ethanol at a molar ratio of Bi:Ti = 1:2, stir until clear and transparent, and then add it to solution a in step 1 to obtain solution b; Step 3: dissolving sodium hydroxide NaOH in deionized water and stirring to obtain a clear and transparent aqueous solution c, which is then added to the solution b in step 2, and stirred to obtain a light yellow precursor solution d; Step 4: Place the precursor solution d into a stainless steel reactor lined with polytetrafluoroethylene, and then place the reactor into a blast drying oven, and use a two-step heating method for hydrothermal synthesis (Bi 0.5 Na 0.5 )TiO3 powder; Step 5: Wash the product after the reaction until it is neutral, then place it in a drying oven for drying, and then grind and sieve the dried powder to obtain a light yellow (Bi 0.5 Na 0.5 )TiO3 powder.

[0008] In the above technical solution, the concentration of NaOH in step 3 is 6-14 mol / L, preferably 12 mol / L.

[0009] In the above technical solution, the two-step heating method in step 4 is: Step 1: Heat the reactor to the specified temperature and time; Step 2: After the first step of heating is completed, the reactor is cooled to the specified temperature and then kept warm. Then, the reactor is taken out of the drying oven and naturally cooled to room temperature.

[0010] In the above technical solution, the specific steps are as follows: Step 1: Dissolve 3.469 g of bismuth nitrate pentahydrate Bi(NO3)3•5H2O in 5 ml of deionized water, add 5 ml of dilute nitric acid, and stir for 10 minutes to obtain a clear and transparent solution a; Step 2: According to the molar ratio of Bi:Ti = 1:2, 4.9172 g of tetrabutyl titanate Ti(OC4H9)4 was dissolved in 5 ml of anhydrous ethanol, stirred until clear and transparent, and then added to the solution a in step 1 to obtain solution b; Step 3: Dissolve 38.4 g of sodium hydroxide NaOH in 40 ml of deionized water, stir for 40 minutes to obtain a clear and transparent aqueous solution c, then add it to the solution b in step 2, and stir for another 30 minutes to obtain a light yellow precursor solution d; Step 4: Place the precursor solution d into a stainless steel reactor lined with polytetrafluoroethylene, and then place the reactor into a blast drying oven, and use a two-step heating method for hydrothermal synthesis (Bi 0.5 Na 0.5 )TiO3 powder; Step 5: Wash the product after the reaction until it is neutral, then place it in a drying oven at 80°C for 8 hours, and then grind and sieve the dried powder to obtain a light yellow (Bi 0.5 Na 0.5 )TiO3 powder.

[0011] In the above technical solution, the concentration of sodium hydroxide NaOH in step 3 is 6-14 mol / L.

[0012] In the above technical solution, the concentration of the sodium hydroxide NaOH in step 3 is preferably 12 mol / L.

[0013] In the above technical solution, the two-step heating method in step 4 is: Step 1: Heat the reactor to 170-200°C for 0-30 minutes; Step 2: After the first step of heating is completed, the reactor is cooled to 160°C and kept warm for 5 hours. Then, the reactor is taken out of the drying oven and naturally cooled to room temperature.

[0014] In the above technical solution, the heating temperature and time of the reactor in the first step are preferably 180° C. and 30 minutes.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention uses a two-step heating method to hydrothermally synthesize bismuth titanate nanopowder material, which has the characteristics of simple process, low cost and mass production. The prepared powder material is a rhombohedral phase (Bi 0.5 Na 0.5)TiO3, whose particles are spherical aggregates composed of 50 nm cubes with an average size of 450 nm; and the obtained BNT powder has good sintering properties and can be sintered into a relative density of more than 95% (Bi 0.5 Na 0.5 )TiO3 ceramics, the (Bi 0.5 Na 0.5 )TiO3 ceramics have good ferroelectric properties, and their maximum polarization intensity, remnant polarization intensity and coercive field are 40.02 μC / cm 2 , 27.78 μC / cm 2 and 87.5 kV / cm, which have good ferroelectric properties compared with the ceramics fired by the traditional solid phase synthesis method. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0017] Figure 1 The XRD patterns of BNT powders prepared by the two-step heating method of the present invention at different heating temperatures in the first step and the XRD patterns of BNT powders prepared by a conventional hydrothermal synthesis method; Figure 2 This is a scanning electron microscope photo of bismuth titanate nanopowder prepared in the present invention; Figure 3 The XRD patterns of bismuth titanate nanopowders prepared in the first step of the present invention at different holding times are shown; Figure 4 The XRD patterns of bismuth titanate nanopowders prepared by the present invention at different mineralizer concentrations; Figure 5 The hysteresis loop is the BNT ceramic fired by the BNT powder prepared by the present invention. DETAILED DESCRIPTION

[0018] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only embodiments of a part of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention. Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art.

[0019] The present invention provides a bismuth titanate nanopowder material, wherein the powder material is a rhombohedral phase (Bi 0.5 Na 0.5 )TiO3, whose particles are spherical aggregates composed of 50 nm cubes with an average size of 450 nm.

[0020] The invention also provides a sodium bismuth titanate powder material, wherein bismuth nitrate pentahydrate Bi(NO3)3·5H2O, tetrabutyl titanate Ti(OC4H9)4, and sodium hydroxide NaOH are solutes, and deionized water, dilute nitric acid, and anhydrous ethanol are used as solvents to prepare a precursor solution, and at the same time, sodium hydroxide is also used as a mineralizer for a hydrothermal reaction.

[0021] The present invention also provides a method for preparing sodium bismuth titanate powder material, the specific steps of which are as follows: Step 1: dissolving bismuth nitrate pentahydrate Bi(NO3)3·5H2O in ionized water, adding dilute nitric acid and stirring to obtain a clear and transparent solution a; Step 2: Dissolve tetrabutyl titanate Ti(OC4H9)4 in anhydrous ethanol at a molar ratio of Bi:Ti = 1:2, stir until clear and transparent, and then add it to solution a in step 1 to obtain solution b; Step 3: dissolving sodium hydroxide NaOH in deionized water and stirring to obtain a clear and transparent aqueous solution c, which is then added to the solution b in step 2, and stirred to obtain a light yellow precursor solution d; Step 4: Place the precursor solution d into a stainless steel reactor lined with polytetrafluoroethylene, and then place the reactor into a blast drying oven, and use a two-step heating method for hydrothermal synthesis (Bi 0.5 Na 0.5 )TiO3 powder; Step 5: Wash the product after the reaction until it is neutral, then place it in a drying oven for drying, and then grind and sieve the dried powder to obtain a light yellow (Bi 0.5 Na 0.5 )TiO3 powder.

[0022] As an optional implementation, the concentration of NaOH in step 3 is 6-14 mol / L, preferably 12 mol / L.

[0023] In the above technical solution, the two-step heating method in step 4 is: Step 1: Heat the reactor to the specified temperature and time; Step 2: After the first step of heating is completed, the reactor is cooled to the specified temperature and then kept warm. Then, the reactor is taken out of the drying oven and naturally cooled to room temperature.

[0024] As an optional implementation method, the specific steps of the preparation method are as follows: Step 1: Dissolve 3.469 g of bismuth nitrate pentahydrate Bi(NO3)3•5H2O in 5 ml of deionized water, add 5 ml of dilute nitric acid, and stir for 10 minutes to obtain a clear and transparent solution a; Step 2: According to the molar ratio of Bi:Ti = 1:2, 4.9172 g of tetrabutyl titanate Ti(OC4H9)4 was dissolved in 5 ml of anhydrous ethanol, stirred until clear and transparent, and then added to the solution a in step 1 to obtain solution b; Step 3: Dissolve 38.4 g of sodium hydroxide NaOH in 40 ml of deionized water, stir for 40 minutes to obtain a clear and transparent aqueous solution c, then add it to the solution b in step 2, and stir for another 30 minutes to obtain a light yellow precursor solution d; Step 4: Place the precursor solution d into a stainless steel reactor lined with polytetrafluoroethylene, and then place the reactor into a blast drying oven, and use a two-step heating method for hydrothermal synthesis (Bi 0.5 Na 0.5 )TiO3 powder; Step 5: Wash the product after the reaction until it is neutral, then place it in a drying oven at 80°C for 8 hours, and then grind and sieve the dried powder to obtain a light yellow (Bi 0.5 Na 0.5 )TiO3 powder.

[0025] As an optional implementation manner, the concentration of sodium hydroxide NaOH in step 3 is 6-14 mol / L.

[0026] As an optional implementation, the concentration of the sodium hydroxide NaOH in step 3 is preferably 12 mol / L.

[0027] As an optional implementation, the two-step heating method in step 4 is: Step 1: Heat the reactor to 170-200°C for 0-30 minutes; Step 2: After the first step of heating is completed, the reactor is cooled to 160°C and kept warm for 5 hours. Then, the reactor is taken out of the drying oven and naturally cooled to room temperature.

[0028] As an optional implementation, the heating temperature and time of the reactor in the first step are preferably 180° C. and 30 minutes.

[0029] The specific embodiments of the present invention are described in detail below: Example 1 Step 1: Dissolve 3.469 g of bismuth nitrate pentahydrate in 5 ml of deionized water, add 5 ml of dilute nitric acid, and stir for 10 minutes to obtain a clear and transparent solution a. Then, according to the molar ratio of Bi:Ti = 1:2, dissolve 4.9172 g of tetrabutyl titanate in 5 ml of anhydrous ethanol, stir until clear and transparent, and add it to solution a to obtain solution b. Then, dissolve 38.4 g of NaOH in 40 mL of deionized water at a NaOH concentration of 12 mol / L, stir for 40 minutes to obtain a clear and transparent aqueous solution c, and then add aqueous solution c to solution b. After stirring for 30 minutes, a light yellow precursor solution d is obtained.

[0030] Step 2: Place the precursor solution d in a stainless steel reactor lined with polytetrafluoroethylene, then place the reactor in a forced air drying oven and perform a hydrothermal reaction by a two-step heating method: heat the reactor to 170°C, 180°C and 200°C respectively, and keep the temperature for 30 minutes, then cool to 160°C and keep the temperature for 5 hours. After the reaction is completed, take the reactor out of the drying oven and cool it naturally to room temperature.

[0031] Step 3: Wash the product after the reaction until it is neutral, and then place it in a drying oven at 80°C for 8 hours. Grind and sieve the dried powder to obtain a light yellow reactant powder.

[0032] From the above experiments, we can know that: The reactor was heated to 170 °C and kept warm for 30 minutes. Under the same other conditions, the XRD diffraction peaks of the powder synthesized by the two-step heating method were low and broad, indicating that it had not yet completely crystallized into a rhombohedral phase (Bi 0.5 Na 0.5 )TiO3 (see Figure 1 ), the average particle size of which is 180 nm, forming an amorphous aggregate (see Figure 2 (a)).

[0033] The dry reactor was heated to 180 °C and kept warm for 30 minutes. Under the condition that other conditions remained unchanged, the XRD diffraction peaks of the powder synthesized by the two-step heating method were high and sharp, and the crystal structure was rhombohedral phase (Bi 0.5 Na 0.5 )TiO3 (see Figure 1 ), whose particles are aggregates composed of 50nm cubes with an average size of 450nm (see Figure 2 (b)).

[0034] The dry reactor was heated to 200 °C and kept warm for 30 minutes. Under the same other conditions, the crystal structure of the powder synthesized by the two-step heating method was also rhombohedral (Bi 0.5 Na0.5 )TiO3, but the XRD diffraction peak intensity is relatively low, indicating that its crystal quality is relatively poor (see Figure 1 ), the particle morphology is spherical, and the average size is 500 nm (see Figure 2 (c)).

[0035] Therefore, by Figure 1 and Figure 2 It can be seen that in the first step of the two-step heating method, the reactor was heated to 180 °C and kept warm for 30 minutes to prepare the rhombohedral phase (Bi 0.5 Na 0.5 )TiO3 powder is best.

[0036] Example 2 Step 1: Dissolve 3.469 g of bismuth nitrate pentahydrate in 5 ml of deionized water, add 5 ml of dilute nitric acid, and stir for 10 minutes to obtain a clear and transparent solution a. Dissolve 4.9172 g of tetrabutyl titanate in 5 ml of anhydrous ethanol at a molar ratio of Bi:Ti = 1:2, stir until clear and transparent, and add it to solution a to obtain solution b. Dissolve 38.4 g of NaOH in 40 ml of deionized water at a NaOH concentration of 12 mol / L, stir for 40 minutes, and obtain a clear and transparent aqueous solution c. Then add aqueous solution c to solution b and stir for 30 minutes to obtain a light yellow precursor solution d.

[0037] Step 2: The precursor solution d was placed in a stainless steel reactor with a polytetrafluoroethylene liner, and then the reactor was placed in a forced air drying oven for a hydrothermal reaction by a two-step heating method, where the reactor was heated to 180°C, then kept warm for 0, 30, and 60 minutes, respectively, and then cooled to 160°C for 5 hours. Then, the reactor was taken out of the drying oven and naturally cooled to room temperature.

[0038] Step 3: Wash the product after the reaction until it is neutral, and then place it in a drying oven at 80°C for 8 hours. Grind and sieve the dried powder to obtain a light yellow reactant powder.

[0039] From the above experiments, we can know that: Heat the reactor to 180 °C and keep it warm for 10 minutes. When other conditions remain unchanged, the XRD diffraction peak intensity of the powder synthesized by two-step hydrothermal heating is relatively low, showing that (Bi 0.5 Na 0.5 )TiO3 crystal phase and Bi 12 TiO 20 Crystalline phases coexist (see Figure 3 ).

[0040] Heat the reactor to 180 °C and keep it warm for 30 minutes. Under the condition that other conditions remain unchanged, the XRD diffraction peaks of the powder synthesized by two-step heating hydrothermal method are strong and sharp, and the crystal structure is rhombohedral phase (Bi 0.5 Na 0.5 ) Single phase of TiO3 (see Figure 3 ).

[0041] Heat the dry reactor to 180 °C and keep it warm for 60 minutes. Under the condition that other conditions remain unchanged, the XRD diffraction peak intensity of the powder synthesized by two-step hydrothermal heating is relatively strong, but it also shows (Bi 0.5 Na 0.5 )TiO3 crystal phase and Bi 12 TiO 20 Crystalline phases coexist (see Figure 3 ).

[0042] Therefore, by Figure 3 It can be seen that when the drying oven is heated for 30 minutes, the prepared rhombohedral phase (Bi 0.5 Na 0.5 )TiO3 powder is best.

[0043] Example 3 Step 1: Dissolve 3.469 g of bismuth nitrate pentahydrate in 5 ml of deionized water, add 5 ml of dilute nitric acid, and stir for 10 minutes to obtain a clear and transparent solution a. Dissolve 4.9172 g of tetrabutyl titanate in 5 ml of anhydrous ethanol at a molar ratio of Bi:Ti = 1:2, stir until clear and transparent, and add it to solution a to obtain solution b. Weigh NaOH at a NaOH concentration of 6, 9, 12, and 14 mol / L, respectively, dissolve it in 40 ml of deionized water, stir for 40 minutes, and obtain a clear and transparent aqueous solution c. Then add aqueous solution c to solution b and stir for 30 minutes to obtain four light yellow precursor solutions d.

[0044] Step 2: The four precursor solutions d were placed in stainless steel reactors lined with polytetrafluoroethylene, and then the reactors were placed in a forced air drying oven for hydrothermal reaction by a two-step heating method. The forced air drying oven was heated to 180°C for 30 minutes, then cooled to 160°C and kept warm for 5 hours. Then, the reactor was taken out of the drying oven and cooled naturally to room temperature.

[0045] Step 3: Wash the reaction product until it is neutral, then place it in a drying oven at 80°C for 8 hours, and then grind and sieve the dried powder to obtain a light yellow powder.

[0046] From the above experiments, we can know that: The powder synthesized from the precursor solution prepared with a NaOH concentration of 6 mol / L showed a low and broad XRD diffraction peak, indicating that the (Bi 0.5 Na 0.5 )TiO3 crystal phase (see Figure 4 ).

[0047] The powder synthesized from the precursor solution prepared with NaOH concentration of 9 mol / L (Bi 0.5 Na 0.5 )The XRD diffraction peak intensity of TiO3 crystal phase has increased, but (Bi 0.5 Na 0.5 )TiO3 crystal phase (see Figure 4 ).

[0048] The powder prepared from the precursor solution with NaOH concentration of 12 mol / L (Bi 0.5 Na 0.5 )The XRD diffraction peak of TiO3 crystal phase is sharp, and the intensity increases sharply, indicating that the reaction products are all (Bi 0.5 Na 0.5 )TiO3 (see Figure 4 ).

[0049] The powder prepared from the precursor solution with NaOH concentration of 14 mol / L (Bi 0.5 Na 0.5 )The XRD diffraction peak of TiO3 crystal phase is sharp and the intensity is also increased, but Bi 12 TiO 20 The diffraction peaks of the crystal phase show (Bi 0.5 Na 0.5 )TiO3 crystal phase and Bi 12 TiO 20 Crystalline phases coexist (see Figure 4 ).

[0050] Therefore, by Figure 4 It can be seen that when the NaOH concentration is 12 mol / L, the prepared rhombohedral phase (Bi 0.5 Na 0.5 )TiO3 powder is best.

[0051] Example 4 Control group: one-step heating method was used for hydrothermal reaction preparation (Bi 0.5 Na 0.5 )TiO3 powder.

[0052] Step 1: Dissolve 3.469 g of bismuth nitrate pentahydrate in 5 ml of deionized water, add 5 ml of dilute nitric acid, and stir for 10 minutes to obtain a clear and transparent solution a. Dissolve 4.9172 g of tetrabutyl titanate in 5 ml of anhydrous ethanol at a molar ratio of Bi:Ti = 1:2, stir until clear and transparent, and add it to solution a to obtain solution b. Dissolve 38.4 g of NaOH in 40 ml of deionized water at a NaOH concentration of 12 mol / L, stir for 40 minutes, and obtain a clear and transparent aqueous solution c. Then add aqueous solution c to solution b, stir for 30 minutes, and obtain a light yellow precursor solution d.

[0053] Step 2: Place the precursor solution d into a stainless steel reactor with a polytetrafluoroethylene lining, and then place the reactor in a forced air drying oven. Use the usual one-step heating method to carry out the hydrothermal reaction. Heat the forced air reactor to 180°C and keep it warm for 6 hours. Then, take the reactor out of the drying oven and cool it naturally to room temperature.

[0054] Step 3: Wash the product after the reaction until it is neutral, then place it in a drying oven at 80°C and dry it for 8 hours. Grind and sieve the dried powder to obtain a light yellow product powder.

[0055] From the above experiments, we can know that: The powder synthesized by the conventional one-step heating method for hydrothermal reaction at 180℃ for 6 hours showed relatively strong XRD diffraction peaks, but except for (Bi 0.5 Na 0.5 ) Bi was also detected in TiO3 crystal phase 12 TiO 20 Crystalline phase (see Figure 1 ), the particle morphology is spherical, the average size is 520 nm, and needle-shaped or rod-shaped Bi 12 TiO 20 The second phase (see Figure 2 (d)).

[0056] By comparing Example 1, Example 2, Example 3 and Example 4, it can be seen that compared with the one-step heating method of Example 4, the crystal structure of the powder synthesized by the two-step heating method of the present invention is a rhombohedral phase (Bi 0.5 Na 0.5 )TiO3 (see Figure 1 ), whose particles are aggregates composed of 50 nm cubes with an average size of 450 nm (see Figure 2 (b)), prepared by the present invention (Bi 0.5 Na 0.5)TiO3 powder is used as raw material, and bismuth titanate nanoceramics fired at 1100℃ for 4 hours have good ferroelectric properties (see Figure 5 ). Its relative density is above 95%, and its maximum polarization intensity, residual polarization intensity and coercive field are 40.02μC / cm 2 、27.78μC / cm 2 and 87.5 kV / cm, proving that the (Bi 0.5 Na 0.5 )TiO3 powder has broad application prospects in the fields of bismuth titanate nanoceramics, bismuth titanate nanoceramics and thermosensitive ceramics.

[0057] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A bismuth titanate nanopowder material, characterized in that: The powder material is a rhombohedral phase (Bi 0.5 Na 0.5 )TiO3, whose particles are spherical aggregates composed of 50 nm cubes with an average size of 450 nm.

2. The sodium bismuth titanate powder material according to claim 1, characterized in that: The main preparation raw materials include: bismuth nitrate pentahydrate Bi(NO3)3·5H2O, tetrabutyl titanate Ti(OC4H9)4, and sodium hydroxide NaOH as solutes, and deionized water, dilute nitric acid and anhydrous ethanol are used as solvents to prepare the precursor solution. At the same time, sodium hydroxide NaOH is also used as a mineralizer for the hydrothermal reaction.

3. A method for preparing the sodium bismuth titanate powder material according to claim 1, characterized in that: The specific steps are as follows: Step 1: dissolving bismuth nitrate pentahydrate Bi(NO3)3·5H2O in ionized water, adding dilute nitric acid and stirring to obtain a clear and transparent solution a; Step 2: Dissolve tetrabutyl titanate Ti(OC4H9)4 in anhydrous ethanol at a molar ratio of Bi:Ti = 1:2, stir until clear and transparent, and then add it to solution a in step 1 to obtain solution b; Step 3: dissolving sodium hydroxide NaOH in deionized water and stirring to obtain a clear and transparent aqueous solution c, which is then added to the solution b in step 2, and stirred to obtain a light yellow precursor solution d; Step 4: Place the precursor solution d into a stainless steel reactor lined with polytetrafluoroethylene, and then place the reactor into a blast drying oven, and use a two-step heating method for hydrothermal synthesis (Bi 0.5 Na 0.5 )TiO3 powder; Step 5: Wash the product after the reaction until it is neutral, then place it in a drying oven for drying, and then grind and sieve the dried powder to obtain a light yellow (Bi 0.5 Na 0.5 )TiO3 powder.

4. The method for preparing sodium bismuth titanate powder material according to claim 3, characterized in that: The two-step heating method described in step 4 is: Step 1: Heat the reactor to the specified temperature and time; Step 2: After the first step of heating is completed, the reactor is cooled to the specified temperature and then kept warm. Then, the reactor is taken out of the drying oven and naturally cooled to room temperature.

5. The method for preparing sodium bismuth titanate powder material according to claim 4, characterized in that: The specific steps are as follows: Step 1: Dissolve 3.469 g of bismuth nitrate pentahydrate Bi(NO3)3•5H2O in 5 ml of deionized water, add 5 ml of dilute nitric acid, and stir for 10 minutes to obtain a clear and transparent solution a; Step 2: According to the molar ratio of Bi:Ti = 1:2, 4.9172 g of tetrabutyl titanate Ti(OC4H9)4 was dissolved in 5 ml of anhydrous ethanol, stirred until clear and transparent, and then added to the solution a in step 1 to obtain solution b; Step 3: Dissolve 38.4 g of sodium hydroxide NaOH in 40 ml of deionized water, stir for 40 minutes to obtain a clear and transparent aqueous solution c, then add it to the solution b in step 2, and stir for another 30 minutes to obtain a light yellow precursor solution d; Step 4: Place the precursor solution d into a stainless steel reactor lined with polytetrafluoroethylene, and then place the reactor into a blast drying oven, and use a two-step heating method for hydrothermal synthesis (Bi 0.5 Na 0.5 )TiO3 powder; Step 5: Wash the product after the reaction until it is neutral, then place it in a drying oven at 80°C for 8 hours, and then grind and sieve the dried powder to obtain a light yellow (Bi 0.5 Na 0.5 )TiO3 powder.

6. The method for preparing sodium bismuth titanate powder material according to claim 5, characterized in that: The concentration of sodium hydroxide NaOH described in step 3 is 6~14 mol / L.

7. The method for preparing sodium bismuth titanate powder material according to claim 6, characterized in that: The concentration of sodium hydroxide NaOH in step 3 is preferably 12 mol / L.

8. The method for preparing sodium bismuth titanate powder material according to claim 5, characterized in that: The two-step heating method described in step 4 is: Step 1: Heat the reactor to 170-200°C for 0-30 minutes; Step 2: After the first step of heating is completed, the reactor is cooled to 160°C and kept warm for 5 hours. Then, the reactor is taken out of the drying oven and naturally cooled to room temperature.

9. The method for preparing sodium bismuth titanate powder material according to claim 6, characterized in that: The heating temperature and time of the reaction kettle in the first step are preferably 180° C. and 30 minutes.

Citation Information

Patent Citations

  • Method for synthesizing Bi0.5Na0.5TiO3 spheroidal particles by microwave hydrothermal method

    CN101525239A

  • Method for synthetizing leadless piezoelectric ceramic K0.65Na0.35NbO3 powder adopting two-step hydrothermal method

    CN104098334A

  • Method for preparing uniform nano-microspherical Na0.5Bi0.5TiO3 crystals

    CN107055610A

  • Preparation method of bismuth sodium titanate powder

    CN107089680A

  • Spherical sodium bismuth titanate powder prepared by hydrothermal method and preparation method thereof

    CN109399708A